PEMBUATAN DAN KARAKTERISASI BIODIESEL DARI MINYAK BUNGA MATAHARI DAN METANOL DENGAN KATALIS NaOH - -, Sukamta; Endriyani, Sunarti; Anita, Fitri (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2008)
Biodiesel is fuel made of seed oil and has potential to be used as substitute of crude oil. In this experimental work, it was used sun flower seed oil as a raw material of biodiesel.The aims of the research were to study a transesterification reaction of trigli-seryde of a sun flower seed oil and methanol and to attain the optimum conditions of the process to produce good quality of biodiesel. This research were done by mixing sun flower seed oil, methanol and catalyst with oil and methanol volume ratios were 1: 6 and 1:9 respectively. The ester produced were then characterised. The experiments resultant showed that the best quality of biodiesel were attained when the volume ratio between oil and methanol was 1:6 at temperature of reaction of 50oC and time of reaction of 90 minute. The characteristic of the oil produced were specific gravity 60/60 °F = 0,8846 ; viscosity kinematic = 4,562 cSt; pour point = 25,7°F ; flash point = 115 °F, and conversion of 32,42%. This characteristic in the range of the standard of biodiesel based on the letter of Ketua Badan Standarisasi Nasional No.04 – 7182 – 2006 about biodiesel.